Effects of anemia on pregnancy outcomes at Manipal Teaching Hospital - Mahato, Vibha; Shrestha, Pravin (Birat Journal of Health Sciences, 2020)
Introduction: Anemia is one of the most common disorders affecting the pregnant women in the developing countries like Nepal. Anemia during pregnancy is commonly associated with adverse pregnancy outcomes. Identifying anemia in pregnancy and knowing its common complications will help improve maternal quality care. Objectives: The objective - was to assess the effects of anemia on pregnancy outcome at Manipal Teaching Hospital Methodology: This cross sectional study was conducted in Manipal Teaching Hospital from September 2019 to April 2020. A total of 200 anemic pregnantladies attending obstetrics Out Patient Department were selected.Hemoglobinlevel was taken as criteria for deciding anemia and to classify severity of anemia.Anemia in pregnancy is defined by World Health Organization as hemoglobin level less than 11 gm/dl, and hemoglobin concentration of 10–10.9 g/dl, 7–9.9 g/dl, and <7 g/ dl was considered as mild, moderate, and severe anemia, respectively . All were treated depending on severity of anemia and followed up for maternal and perinatal outcome.Data was collected in Microsoft Excel and analyzed by using SPSS version 16. Result: We found moderate anemia in 129 (64.5%) cases followed by mild in 61(30.5%) and severe in 10(5%) cases. Common maternal complications in anemic patients werepremature rupture of membranein 30 (15%) cases and Urinary Tract Infection in 30(15%) cases.During puerperiumPostpartum Hemorrhage was observed in 12(6%) and wound infection in 9 (4.5%) cases of anemic patient. High incidence of adverse fetal outcome in the form of preterm in 39 (19.5%), Intrauterine growth restrictionin 23(11.5%), Intensive Care Unitadmission in28(14%),low birth weight in41(20.5%) and Intrauterine Death in4(2%) cases of anemic patients were seen. Conclusion: Maternal infection and adverse perinatal outcome in form of intrauterine growth restriction, Intensive Care Unitadmission, low birth weight and perinatal death were significantly associated with anemia in pregnancy.